Diseño de un aplicativo web y móvil para la gestión de información en la clínica odontológica “PCF" ubicado en la ciudad de Latacunga. - Chauca Toapanta, Alex Ricardo (2021)
The Dental Clinic "PCF" has worked to improve the control of its activities, quality and patient care, in this way to be able to identify specific problems or defects that exist within the institution at the time of carrying out its processes, and to follow up. to the dental health of patients. The development of the web and mobile system arises from the need to streamline and optimize processes, achieving a better organization and registration of clinic information. The proposed system helps to improve the information management of the clinic because the process is done manually. For this reason, it was agreed to carry out the application, quickly and easily obtaining information on the clinical history, patient registration, treatments, appointment registration, payments and other services that the dental clinic has. The management system is designed to meet the needs and specific points of the clinic, trying to adapt to its requirements to meet the needs of the patient, reduce time and work. In addition, it will increase productivity and the rapid detection of difficulties that may arise when completing the treatment. Treat the clinic as an entity dedicated to adapting to new computer tools and methods for accessing and managing information for both clients and clinic staff. Through this new opportunity, benefits are provided within the clinic, improving its quality, streamlining patient care, optimizing information search time, processing information more reliably and eventually better control of the appointment process, thus generating appropriate services for the patient.